2021
DOI: 10.1080/10408398.2021.2009436
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from lotus (Nelumbo nucifera): recent advances in biosynthesis, pharmacokinetics, bioactivity, safety, and industrial applications

Abstract: Different parts of lotus (Nelumbo nucifera Gaertn.) including the seeds, rhizomes, leaves, and flowers, are used for medicinal purposes with health promoting and illness preventing benefits. The presence of active chemicals such as alkaloids, phenolic acids, flavonoids, and terpenoids (particularly alkaloids) may account for this plant's pharmacological effects. In this review, we provide a comprehensive overview and summarize up-to-date research on the biosynthesis, pharmacokinetics, and bioactivity of lotus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 199 publications
0
6
0
Order By: Relevance
“…However, to the best of our knowledge, a comprehensive state-of-the-art review of all available anticancer studies has not been performed. Most of the previous reviews mainly focused on traditional and ethnopharmacological uses, biosynthesis, phytochemical analysis, industrial applications, and broad-spectrum health benefits of N. nucifera in which an overview of anticancer potential represents a minor representation [29,[31][32][33][34]37]. Several prior publications highlighted pharmacological activities of selected phytochemicals of N. nucifera, and these reports did not have a sole focus on cancer [25,35,36,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, a comprehensive state-of-the-art review of all available anticancer studies has not been performed. Most of the previous reviews mainly focused on traditional and ethnopharmacological uses, biosynthesis, phytochemical analysis, industrial applications, and broad-spectrum health benefits of N. nucifera in which an overview of anticancer potential represents a minor representation [29,[31][32][33][34]37]. Several prior publications highlighted pharmacological activities of selected phytochemicals of N. nucifera, and these reports did not have a sole focus on cancer [25,35,36,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…61,62 It is suggested that capsaicin activates thermogenesis via the sympathetic nervous system through physically interacting with the transient receptor potential vanilloid 1 (TRPV1) receptor, leading to weight loss. 60,63 Capsaicin binding to the TRPV1 receptor in sympathetic neurons releases the neuropeptide calcitonin gene-related peptide (CGRP), which regulates energy metabolism. 64,65 Capsaicin has also been proven to enhance lipid oxidation and trigger thermogenesis in BAT by increasing UCP1 activity, enhancing energy expenditure and lowering body weight.…”
Section: How To Target Energy Balancementioning
confidence: 99%
“…Lotus has earned the moniker of “sacred lotus” in China due to its significant benefits and has long been revered as a symbol of purity and spiritual transcendence in traditional Chinese culture, Buddhism, and Hinduism. The total cultivated land area of lotus in China is estimated to be over 330,000 ha (Wang et al, 2021b). To date, approximately 4500 cultivars are available in the lotus germplasm (Qi et al, 2022), which have been obtained primarily through traditional crossing, while a few were developed by chemical or space‐induced mutations.…”
Section: Introductionmentioning
confidence: 99%